Smart Aquarium Based On Internet of Things - Hardyanto, R Hafid; Ciptadi, Prahenusa Wahyu; Asmara, Andik (Journal of Business and Information Systems (e-ISSN: 2685-2543), 2019)
: IoT technology has been widely applied in everyday life. IoT technology has been applied to smart home, smart city, and several supporting applications implemented by IoT technology. IoT technology can also be applied in hobby of keeping fish. The aquarium system that is sold in the market today is an ordinary aquarium. The aquarium system on the market today is already interesting, with a collection of plants and fish in the aquarium, but the problems that occur if the aquarium is stored in the house will be less to the needs of sunlight. Sometimes the lights that have a diaquarium are not adapted to the needs of plants or fish in the aquarium. Another problem is the provision of fish feed that is still manual. Sometimes aquarium owners must provide fish feed manually at least once a day. This is very troublesome if the owner of the aquarium has a very high activity, so the risk of forgetting to feed fish is very high. To overcome the problems mentioned above, it is necessary to have an aquarium system that is eyecatching and completely automated, both in terms of lighting and aspects of fish feeding. A smart aquarium system that can accommodate aquarium hobbyists with all the activities owned by aquarium owners. In this paper, we designed a new smart aquarium system using IoT devices